Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Bina Cipta Rasa Sejati Medan - Sari, Putri; Wahyuni, Neni Sri; Supriadi, Supriadi (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2025)
The purpose of this study was to determine and analyze the effect of motivation and work environment on employee performance at PT Bina Cipta Rasa Sejati Medan. The sample in this study amounted to 70 employees. The analysis method used in this study involves two independent variables, namely motivation and work environment and one dependent variable, namely employee performance. The results of this study indicate that motivation partially has a significant effect on employee performance at PT Bina Cipta Rasa Sejati Medan. The work environment partially has a significant effect on employee performance at PT Bina Cipta Rasa Sejati Medan. Motivation and work environment simultaneously have a significant effect on employee performance at PT Bina Cipta Rasa Sejati Medan.